Persistent lateral elbow pain from overlooked posterolateral impingement of the elbow: a literature review and guidance for treatment - Gur-Aziz Singh Sidhu; Niyam Amanullah; Harjot Kaur; Saphalya Pattnaik; Neil Ashwood; Andrew Peter Dekker; Harpal Singh Selhi (Clinics in Shoulder and Elbow)
Posterolateral impingement is sometimes diagnosed as a cause of refractory elbow pain, often after other treatments have been tried for common conditions such as lateral epicondylitis (tennis elbow) or subtly different conditions common in throwing athletes, such as valgus extension overload syndrome. Arthroscopic surgical treatment is effective when targeting abnormal anatomy such as plicae folds. Partial excision of the olecranon must be undertaken with caution because it can lead to instability. This systematic review of the current literature uses a narrative synthesis to identify anatomical morphological variations of the olecranon, humeral and capitellar geometry, and overloading of the lateral part of the elbow as causative factors for this condition and discusses how arthroscopic techniques can resolve symptoms. Further understanding of the static and dynamic anatomy of the lateral part of the elbow will help to develop future treatment and preventive strategies.